Cell Deformation at the Air-Liquid Interface Evokes Intracellular Ca2+ Increase and ATP Release in Cultured Rat Urothelial Cells - Wen, Jiliang; Chen, Zhenghao; Zhao, Mengmeng; Zu, Shulu; Zhao, Shengtian; Wang, Shaoyong; Zhang, Xiulin (Frontiers in Physiology, 2021)
Urothelial cells have been implicated in bladder mechanosensory transduction, and thus, initiation of the micturition reflex. Cell deformation caused by tension forces at an air-liquid interface (ALI) can induce an increase in intracellular Ca2+ concentration ([Ca2+]i) and ATP release in some epithelial cells. In this study, we aimed to examine the cellular mechanisms underlying ALI-induced [Ca2+]i increase in cultured urothelial cells. The ALI was created by stopping the influx of the perfusion but maintaining efflux. The [Ca2+]i increase was measured using the Ca2+ imaging method. The ALI evoked a reversible [Ca2+]i increase and ATP release in urothelial cells, which was almost abolished by GdCl3. The specific antagonist of the transient receptor potential vanilloid (TRPV4) channel (HC0674) and the antagonist of the pannexin 1 channel (10panx) both diminished the [Ca2+]i increase. The blocker of Ca2+-ATPase pumps on the endoplasmic reticulum (thapsigargin), the IP3 receptor antagonist (Xest-C), and the ryanodine receptor antagonist (ryanodine) all attenuated the [Ca2+]i increase. Degrading extracellular ATP with apyrase or blocking ATP receptors (P2X or P2Y) with pyridoxalphosphate-6-azophenyl-2',4'-disulfonic acid (PPADS) significantly attenuated the [Ca2+]i increase. Our results suggest that both Ca2+ influx via TRPV4 or pannexin 1 and Ca2+ release from intracellular Ca2+ stores via IP3 or ryanodine receptors contribute to the mechanical responses of urothelial cells. The release of ATP further enhances the [Ca2+]i increase by activating P2X and P2Y receptors via autocrine or paracrine mechanisms.